(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Giant cell tumor (GCT) or osteoclastoma are rare benign bone tumor and best known for their local aggressiveness and high recurrence. GCT frequently involves tubular long bones (75-90%). Multicentric giant cell tumor is rarer type of GCT. We report a case of a young girl with multicentric GCT. Case History: A 18 years old girl was presented with swelling of right middle finger. X-ray of right hand showed an oval shaped lytic lesion in middle phalanx of right middle finger. Then she underwent open biopsy and histopathologic diagnosis was GCT. Three months later she again developed swelling in left side of mandible. Excision biopsy from left side of mandible confirmed the diagnosis of GCT. Seven months later she again developed swelling in upper part of left humerus. She was then sent to our department for 99mTc-MDP Whole body Bone Scintigraphy. 99mTc-MDP Whole body Bone Scintigraphy with regional SPECT/CT identifies additional three lesions in right 12th rib, left iliac bone and distal left tibia which then confirmed by histopathology. Conclusion: 99mTc-MDP Whole body Bone Scintigraphy with regional SPECT/CT is very much useful in detection of occult lesions in multicentric GCT. Bangladesh J. Nuclear Med. 27(2): 310-312, 2024